Optimalisasi UI/UX Design of an Android-Based Cafe Ordering Application Using the Design Thinking Method (Case Study: Adaa Caffe – Pulo Kemiri, Southeast Aceh) - Putri Nabila; Putri Alasta; Randi Atmaja; Wahyumi Mimbar; Sanjaya Alacsel (Jurnal Armada Informatika, 2026)
Cafe ordering requires customers to understand menus, variants, prices, availability, payment, and order status within a short period. An interface that exposes many options without clear hierarchy can increase errors and cognitive load. This study develops an Android-based cafe ordering UI/UX design for Adaa Caffe, Pulo Kemiri, Southeast Aceh, using Design Thinking. An artifact-oriented design process covers empathize, define, ideate, prototype, and test. User context is represented through hypothetical personas, a customer journey, problem statements, requirements, information architecture, task flows, prototypes, and evaluation scenarios. The result comprises three persona groups, eighteen core needs, five problem statements, twenty-four task scenarios, twelve usability criteria, ten interface risks, and three prototype iterations. The design centers the experience on menu discovery, transparent customization, visible costs, queue status, and error recovery. Traceability inspection shows that every requirement is linked to a problem, interface component, and acceptance scenario. The contribution is a Design Thinking pattern that connects user insight to UI/UX decisions and evaluation evidence. These results indicate design completeness rather than field effectiveness because verified interviews and real-user testing remain outside the study boundary.